Implications of research on effective learning environments for initial teacher education - Conner, Lindsey; Sliwka, Anne (European journal of education, 2014)
As a result of multi-disciplinary research on learning, a consistent and comprehensive body of knowledge on effective learning environments is currently emerging (OECD 2010). While this evidence is increasingly influencing the academic and policy discourse on the improvement and innovation of schools, its impact on the design principles of effective initial teacher education has been limited so far. In this paper, the seven transversal learning principles published in the 2010 OECD publication The Nature of Learning: Using Research to Inspire Practice serve as a framework for systematic reflections on how learning research on effective learning environments can inform initial teacher education and how the seven transversal learning principles can contribute to greater coherence and alignment in initial teacher education programs. We consider the implications of The Nature of Learning and other research on teacher education, alongside international examples of next practice, concluding that initial teacher education should model effective student learning.